2009
DOI: 10.1017/s0007680500002993
|View full text |Cite
|
Sign up to set email alerts
|

Financing Manufacturing Innovation in Argentina, 1890–1930

Abstract: Between 1890 and 1930, Argentina's manufacturers invested in imported machinery. Although they aligned with political allies to advance and protect their companies, their dependence on imported machinery, raw materials, fuel, and expensive skilled labor were obstacles to their success. Two factors slowed the progress of these entrepreneurs: their lack of technological capabilities and the absence of government policies to address the problems entailed in importing foreign machinery. Several political factions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Países con mayor cantidad de artículos en el corpus de financiación de la innovación de 2001 a mayo de 2016 4.5 Dirección de los estudios en financiación de la innovación Los autores que han escrito sobre la financiación de la innovación han tenido diversas formas de abordar el tema. De los 96 artículos revisados en este análisis bibliométrico, hay artículos que se enfocan en el estudio de la financiación de la innovación en empresas de servicios (Demirel & Parris, 2015;Mas-Verdu, 2007;Mulley & Walters, 2014;Probert, Connell, & Mina, 2013) al igual que en empresas manufactureras (Herath, Cranfield, & Henson, 2010;Jack & Lanjouw, 2005;Nivoix & Nguyen, 2012;Pineda, 2009). También hay referencias que tratan específicamente la financiación de la innovación en empresas de alta tecnología (Cockburn & MacGarvie, 2009;Kulatilaka & Lin, 2006;Lethbridge, 2003;Serrasqueiro, Maçãs-Nunes, & da Rocha-Armada, 2016;Xiao, 2011).…”
Section: Figuraunclassified
“…Países con mayor cantidad de artículos en el corpus de financiación de la innovación de 2001 a mayo de 2016 4.5 Dirección de los estudios en financiación de la innovación Los autores que han escrito sobre la financiación de la innovación han tenido diversas formas de abordar el tema. De los 96 artículos revisados en este análisis bibliométrico, hay artículos que se enfocan en el estudio de la financiación de la innovación en empresas de servicios (Demirel & Parris, 2015;Mas-Verdu, 2007;Mulley & Walters, 2014;Probert, Connell, & Mina, 2013) al igual que en empresas manufactureras (Herath, Cranfield, & Henson, 2010;Jack & Lanjouw, 2005;Nivoix & Nguyen, 2012;Pineda, 2009). También hay referencias que tratan específicamente la financiación de la innovación en empresas de alta tecnología (Cockburn & MacGarvie, 2009;Kulatilaka & Lin, 2006;Lethbridge, 2003;Serrasqueiro, Maçãs-Nunes, & da Rocha-Armada, 2016;Xiao, 2011).…”
Section: Figuraunclassified
“…As a result, the technological capabilities of the country remained basic. 32 As studies of nineteenth century Mexico and elsewhere, have shown, as the West pulled away, technological catch-up was a huge entrepreneurial challenge. The new advanced technologies of the West were embedded in quite different institutional, economic and social contexts than in the Rest.…”
Section: Creating Wealth and Poverty In The First Global Economymentioning
confidence: 99%